THE IMPACT OF GREEN BRAND POSITIONING, ATTITUDE, ENVIRONMENTAL CONCERN, GREEN BRAND KNOWLEDGE TOWARD GREEN PURCHASE INTENTION OF MR PRODUCTS IN JAKARTA - Satriohantoro, Mikael; Ruslim, Tommy Setiawan (Graduate Program of Universitas Tarumanagara, 2025)
This reserach aims to examine and discuss the influence of green brand positioning, attitudes, environmental concerns, and knowledge on green brands on purchase intention. The study population consisted of MR product user in Jakarta. This study applied quantitative descriptive methods, and also managed to collect a sample of 212 respondents with criteria, namely a minimum age of 20 years, location of residence, and users of MR products. The total respondents used as samples were 201 respondents, because 11 respondents did not meet the predetermined criteria. This study uses and applies nonprobability sampling with purposive sampling method, and collects data by distributing questionnaires online with the google form application. The results of the data that have been distributed are then collected to be analyzed using the SmartPLS4 application with the Partial Least Square Structural Equation Modeling (PLS-SEM) model. The results of the analysis show that green brand positioning, attitude, environmental concern, and knowledge on green brands have a positive and significant impact on purchase intention. In addition to academic results, this research is also expected to help MR companies or other companies in increasing the purchase intention of their consumers through several variables in this study. And it is hoped that this research can complement the empirical gap that exists in previous research.